Basic vocabulary of an extinct language (Khoton language in Mongolia) - Zhakupov Ж.А.; Abdikarim Н. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2024)
This article presents the findings of the initial phase of studying the Khoton language, which is one of the extinct languages and is not included in the list of world languages. Previous researchers of Khoton considered it only in the historical and ethnological aspect. Therefore, the peculiarity of this work is that the language of the ethnic group is taken as a special object of research. The Khotons living in Mongolia (in Russian and Mongolian languages it is written as “Khoton”, and the original name is “Khotyng”) have not lost their ethnic memory: they know well that they are of Turkic origin. According to the recent census, their number has reached 11,000. Even so, they have lost their native language, and so far there has not been found a person who speaks the Khoton language. However, it is notable that their Khalkha speech incorporates certain Khoton words in the function of the dialect. In modern general linguistics, to assess the relationship of different languages, a focus on the “List of the Swadesh” has been applied. Therefore, the task of creating Swadesh list of the vocabulary of the Khoton language was carried out. In order to clearly prove that the Khoton language belongs to the Turkic languages, the standard Swadesh list which was used by turcologist A.V. Dybo to etymologize the basic Turkic vocabulary, was applied. It is noticed that the Khoton language has an opportunity to take its place among the Turkic languages. Furthermore, a greater number of elements of the Kyrgyz language were identified within the Turkic languages. The ultimate aim of this study is to document and archive the Khoton language as an extinct language. The article was written during the implementation of the grant project AP19675461 “Interdisciplinary study of endangered Turkic languages: the khoton ethnic group in Mongolia”.